PERTANGGUNGJAWABAN PELAKU USAHA BERDENDANG BERGOYANG FESTIVAL 2022 ATAS KETIDAKSESUAIAN JANJI MENURUT UNDANG - UNDANG PERLINDUNGAN KONSUMEN - Naura Afifa Louisa Tindangen, (Prodi Ilmu Hukum Fakultas Hukum Universitas Warmadewa, 2023)
Business operators in carrying out their activities must pay attention to their obligations in serving consumers. Consumer rights are an important element that is the obligation of business operators in carrying out their fulfillment, such as in the case of the Berdendang Bergoyang Festival 2022 where business operators, namely Emvriopro, do not perform their obligations by not compensating ticket owners until now. The ticket owners of the Berdendang Bergoyang Festival 2022 were promised to be refunded for 30-45 days and did not get their right to watch the event until it was finished. Emvriopro has an obligation to compensate ticket holders of the Berdendang Bergoyang Festival 2022 in accordance with the Consumer Protection Act.The purpose of this study is to conduct an analysis of Emvriopro's responsibility as a business operator of the Berdendang Bergoyang Festival 2022 and to know the legal efforts that consumers can make. This research is important so that business people, especially in the music field, can prepare events more maturely to minimize future mistakes. This study was conducted using normative legal methods accompanied by interviews. The results of this study stated that Emvriopro had to compensate as a form of accountability for the obligations violated in fulfilling the rights of ticket owners of the Berdendang Bergoyang Festival 2022. The ticket owner of the Berdendang Bergoyang Festival 2022 can make legal efforts based on the Consumer Protection Law through BPSK or go to court to produce a binding final decision. With this study, it is possible to increase business operators' compliance with future consumer protection laws.